Translational Sepsis Research: Spanning the Divide. Issue 9 (September 2018) - Lewis, Anthony J.; Lee, Janet S.; Rosengart, Matthew R.
Abstract : Objective: Our knowledge of the molecular mechanisms of sepsis has attained exponential growth. Yet, the pillars of its care remain antibiotics, fluid resuscitation, and physiologic support of failing organ systems. The inability to bring biologic breakthroughs to the bedside is not for lack of effort. Over 60 clinical trials of novel therapies, each heavily supported by the momentum of biologic data suggesting clinical utility, have been conducted and have failed to identify benefit. This mass of "negative" clinical data abut an equally towering mound of knowledge of sepsis biology, which collectively have led investigators to ask, "what happened?" Data Sources: Review of published scientific literature via MEDLINE searches using key terms related to the article topics. Study Selection: Original articles, review articles, and systematic reviews were considered. Data Extraction: Articles were selected for inclusion based upon author consensus. Data Synthesis: Here, we present a synthetic review of some of the challenges in translating experimental animal models of sepsis to the bedside. We commence with the concept that the heterogeneity in the kinetics of the sepsis response serves as an important, often underappreciated but surmountable, source of translational impedance. Upon this groundwork, we discuss distinctions between animal experimentation and clinical trial design in the elements for hypothesis testing: cohort selection, power and sample size, randomization and blinding, and timing of intervention. From this concept, we develop a contextual framework for advancing the paradigm of animal-based investigations to facilitate science that transitions from molecule to medicine. Conclusions: A persistent divide exists between the laboratory and clinical research arenas, which may be addressable via systematic targeting of identified translational gaps.